Bullying and cyberbullying among adolescents: prototype game for adolescents in the school environment (Research, Society and Development, 2021)
The aim of this study is to develop a prototype of a game that contributes to health education about Bullying and Cyberbullying among adolescents in the school environment. Technological production research based on design thinking, developed in four stages: 1. Analysis of the data of the bullying questionnaire; 2. Systematic literature review; 3. Search for apps or games available with similar theme in the Google Play Store and App Store; 4. Develop a prototype of a game in simulation style. 99 students answered the questionnaire. In the systematic review, 13 articles were included. In the search of the applications/games, 42 applications were analyzed. The simulation game is called B.S.I.: Bullying Scene Investigation. The theme is investigation, in which the participant searches in the school for clues of possible situations of bullying and cyberbullying and notifies the direction. The game can produce greater awareness about the context of bullying, since it allows promoting the student's protagonism in the school space, the engagement in the fight against violence, the motivation to help victims of bullying and collaboration with the teacher and school management in the strategies of appropriate coping.